One-pot combustion synthesis of Li3VO4-Li4Ti5O12 nanocomposite as anode material of lithium-ion batteries with improved performance - Sha, Y.; Zhang, Z.; Chen, Y.; Lin, Q.; Zhong, Y.; Xu, X.; Shao, Zongping (Pergamon, 2016)
© 2016 Elsevier LtdLi3VO4-decorated Li4Ti5O12 (denoted as V-LTO) composites were synthesized via a facile one-pot cellulose-assisted combustion route. Homogeneous distribution of the Li3VO4 phase to introduce additional lithium ion transport paths in the composites and slight doping of vanadium into the lattice of Li4Ti5O12 phase were realized simultaneously through the one-pot synthesis, resulting in enhanced apparent ionic and electronic conductivity of the electrode materials. The product with optimal V content, i.e., V-LTO (1:8), showed much improved rate capacities compared with the pristine Li4Ti5O12. The effect of vanadium incorporation on the over-discharge capability of anode materials at a lower voltage was also studied, and the V-LTO (1:8) electrode demonstrated a capacity of 193.6 mAh g-1 at a current density of 2000 mA g-1 in the potential window of 0.2-3.0 V, much higher than that of pristine Li4Ti5O12 (141.0 mAh g-1). A fairly good cycling stability was also achieved with a capacity retention ratio of 90.0% after working at 1000 mA g-1 between 0.2 and 3.0 V for 200 times for the V-LTO (1:8) electrode, which is much higher compared with the capacity retention ratio of 73% for electrodes prepared with pristine Li4Ti5O12 under the same condition.